Animating patient stories for medical education: the power of personified storytelling - Benvenuti, David (2025)
Medical animations are widely used in public health education. However, this paper posits that incorporating narrative-based patient stories can be more persuasive than didactic infographics, making them particularly effective in eliciting attitudinal, judgmental, and behavioural changes. Cultural representation in patient education is still not fully explored, especially in Southeast Asia, specifically Singapore, where communities of different ethnic backgrounds coexist. There is a gap in research on how culturally relevant patient stories can be delivered in an informative yet engaging and entertaining manner in a medical context. This project explores how we can devise strategies utilising narrative animation to increase engagement and memory retention in viewers. We discuss creating two short, animated films that aim to entertain whilst communicating the concepts of genetic conditions and hereditary cancer. By documenting the films' creation and highlighting the iterative processes, we show how it was possible to achieve information accuracy with engaging visual storytelling incorporating visual cues for a culturally diverse audience. The paper illustrates the study design and creative decision-making to ascertain how animation and visual storytelling can raise the public’s genetic literacy by educating them about hereditary genetic conditions.